Who Plans the Planning? Architecture, Politics, and Mankind. - Burckhardt, Lucius (Birkhäuser, 2020)
Lucius Burckhardt (1925-2003) setzte sich seit den 1950er-Jahren mit dem Planen und Bauen in der Demokratie auseinander. Seine scharfen Beobachtungen und kritischen Analysen haben die Gestaltung unserer Umwelt, die Lehre in den planenden Berufen und das Verständnis von Stadt grundlegend beeinflusst. Seine Forschungen, die zwischen mächtigen ökonomischen Interessen und widerstreitenden politischen Ansprüchen das Wohl einer Gesamtbevölkerung in den Blick nehmen, sind unentbehrlich, wann und wo immer geplant, gestaltet, gebaut und gewohnt wird. Das Buch versammelt eine neue Auswahl seiner Texte.

From the 1950s, Lucius Burckhardt (1925-2003) focused on planning, design, and construction in a democracy. His astute observations and critical analysis have had a fundamental effect on the design of our environment, on teaching in the architectural/planning professions, and on our understanding of what "city" means. His research, which - between mighty commercial interests and conflicting political aspirations focuses on the benefit for the entire population - is indispensable when and wherever buildings are planned, designed, built, and inhabited. With a new selection of texts, this book ploughs a furrow through Lucius Burckhardt s theory of planning. A collection of important source texts, for the first time available in English.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Städtebau; Gesellschaft; Planungstheorie; Architekturtheorie